2022
DOI: 10.1038/s41536-022-00212-z
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase is required for glomerular renewal in kidneys of adult mice

Abstract: Homeostatic renal filtration relies on the integrity of podocytes, which function in glomerular filtration. These highly specialized cells are damaged in 90% of chronic kidney disease, representing the leading cause of end-stage renal failure. Although modest podocyte renewal has been documented in adult mice, the mechanisms regulating this process remain largely unknown and controversial. Using a mouse model of Adriamycin-induced nephropathy, we find that the recovery of filtration function requires up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Microvasculature density has been shown to decrease in organs of aged mice (Grunewald et al, 2021 ). Because conditional induction of mTert has been reported in vivo to cause the long-term proliferation of several types of stem cells (Sarin et al, 2005 ; Shkreli et al, 2011 ; Montandon et al, 2022 ), we determined whether m Tert expressed from p21 promoter in the lungs of aged mice could affect capillary density that declines with age. We labeled lung parenchyma with CD31 to reveal the vasculature compartment in young and old mice of the 4 genotypes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microvasculature density has been shown to decrease in organs of aged mice (Grunewald et al, 2021 ). Because conditional induction of mTert has been reported in vivo to cause the long-term proliferation of several types of stem cells (Sarin et al, 2005 ; Shkreli et al, 2011 ; Montandon et al, 2022 ), we determined whether m Tert expressed from p21 promoter in the lungs of aged mice could affect capillary density that declines with age. We labeled lung parenchyma with CD31 to reveal the vasculature compartment in young and old mice of the 4 genotypes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that a catalytically inactive mTERT was able to cause proliferation of hair follicle (Sarin et al, 2005 ), skin basal keratinocytes (Choi et al, 2008 ) and kidney podocytes (Shkreli et al, 2011 ). In particular, transient overexpression of catalytically inactive mTert (i-TERT ci mouse model) triggers the clonal expansion of podocyte progenitor cells, however these cells are unable to differentiate when overexpression of mTERT ci is maintained inducing lethal nephropathy (Shkreli et al, 2011 ; Montandon et al, 2022 ). In our p21 +/TertCI model the role of TERT non-canonical function is difficult to reveal because TERT catalytic activity is essential for lung protection.…”
Section: Discussionmentioning
confidence: 99%
“…Microvasculature density has been shown to decrease in organs of aged mice (Grunewald et al , 2021). Because conditional induction of TERT has been reported in vivo to cause the long-term proliferation of several types of stem cells (Sarin et al , 2005; Shkreli et al , 2011; Montandon et al , 2022), we determined whether TERT expressed from p21 promoter in the lungs of aged mice could affect capillary density that declines with age. We labelled lung parenchyma with CD31 to reveal the vasculature compartment in young and old mice of the 4 genotypes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that a catalytically inactive TERT was able to cause proliferation of hair follicle (Sarin et al , 2005), skin basal keratinocytes (Choi et al , 2008) and kidney podocytes (Shkreli et al , 2011). In particular, transient overexpression of catalytically inactive TERT (i-TERT ci mouse model) triggers the clonal expansion of podocyte progenitor cells, however these cells are unable to differentiate inducing lethal nephropathy (Montandon et al , 2022). Overall, we speculate that the decreased expression of p21 favours the expansion of progenitor cells in both p21 +/Tert and p21 +/TertCI mice, however only the mice that express catalytically active telomerase maintain this effect during aging by preventing cellular senescence.…”
Section: Discussionmentioning
confidence: 99%